Taxonomy, karyomorphology and pollen viability of Hymenocallis littoralis (Jacq.) Salisb. (Amaryllidaceae) - Afroz, Sumona; Begum, Kazi Nahida; Saha, Susmita; Hassan, Md Abul; Rahman, M Oliur (Bangladesh Journal of Plant Taxonomy, 2024)
The present study offers the taxonomy, karyomorphology, and pollen-pistil interactions in the bulbous species Hymenocallis littoralis (Jacq.) Salisb. of the family Amaryllidaceae. The genus Hymenocallis is closely allied to Pancratium, however, differs from the later by filament, number and shape of ovule, and seed characteristics. Detailed descriptions and illustrations of H. littoralis are provided, alongside information on its habitat, distribution, examined specimens, and economic significance. A new somatic chromosome number of 2n = 50 is reported for H. littoralis, and this count was not found to be consistent with any of the earlier reports, offering additional insights into its chromosomal characteristics. Furthermore, the study reveals a high pollen viability of 95% in H. littoralis. Bangladesh J. Plant Taxon. 31(2): 265-273, 2024 (December)